Coward, Cromwell - Morris, Marilyn (Teaching History: A Journal of Methods, 1993)
Another book on Cromwell? Barry Coward argues that the massive literature on this enigmatic figure, much of it partisan, is precisely what makes a reevaluation of his character, motives, aims, abilities, and legacy necessary. Moreover, recent revisionist accounts of Charles I’s reign and of the religious tensions of the seventeenth century place Cromwell’s ideas and endeavors in a new light. Coward follows the chronological approach to Cromwell recommended one hundred years ago by S. R. Gardiner, finding Cromwell’s words and actions more (but by no means completely) explicable when viewed in the context of wider events.